Cummins Generator Technologies India Limited : building India's first green factory - Varkkey, Biju; Chetan Soman (London : Indian Institute of Management, Ahmedabad, 2015)
Cummins Generator Technologies India Limited (CGTIL) was in the process of setting up a world-class factory at Ranjangaon based on "lean" production principles. The project team, however, went a step ahead and married "green" with "lean". While lean is about taking the system inefficiencies out, the green is about harmony with nature. The case is about CGTIL's journey of deriving synergies between seemingly conflicting objectives of lean and green.
Originally published in Varkkey, B., & Soman, C. (2015). Cummins Generator Technologies India Limited: Building India's first green factory. PROD0308. Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cummins Generator Technologies India Limited; Lean manufacturing -- India -- Case studies; Manufacturing processes -- Cost control -- India -- Case studies; Production management -- Cost contol -- India -- Case studies; Manufacturing processes -- Environmental aspects -- India -- Case studies; Production management -- Environmental aspects -- India -- Case studies